EFISIENSI PENGGUNAAN INPUT DALAM USAHATANI SELEDRI DI DESA SUMBEREJO, KECAMATAN BATU, KOTA BATU - Isidorus Banggut; Agnes Quartina Pudjiastuti; Ninin Khoirunnisa (BUANA SAINS, 2020)
Efficiency is a production activity that produces an output that is greater and mightier than the other production at the level of the same or production activities with the least input of other production activities and produces the same output. This study aims to analyze production factors that affect the production of celery and analyzed levels of efficiency of the use of the production in farming factors celery in the Sumberejo village. The method of analysis of the data used in this research analytics cobb Douglas and efficiency level. To know the impact of the use of production factor of farming land, ( celery, seeds, fertilizer labor, and pesticide ) analysis is to model cobb Douglas. The use of level analysis done to determine the level of production inputs the use of celery production input in the Sumberejo Village.The use of production inputs ( land, manure, the TSP fertilizer, NPK fertilizer, Urea fertilizer, labor, and pesticide ) simultaneously affects the production of celery. On this fact use, input size of the impact on production and celery seed, manure, the TSP fertilizer, NPK fertilizer, Urea fertilizer, labor, and pesticide did not influence on this fact of celery production in the Sumberejo Village. Technically the use of land as broad input variables, seeds, manure, the TSP fertilizer, urea fertilizer, manpower, and pesticides have efficient it needs to be an increase in the use of it to the technical efficiency of production inputs reached is 1; and variable NPK fertilizer inefficient, so we needed the reduction of their use. While based on the use of the variable size of allocative, seeds, manure, the TSP fertilizer, urea fertilizer, and pesticide not efficient, and NPK fertilizer and labor variable inefficient. Economically, the use of the variable size of having the highest 8,706330748 economic efficiency and variable labor into variables with input by the efficiency of the use of low at 0,00598757.